ANALISIS KEMAMPUAN PEMECAHAN MASALAH SISWA SMP PADA MATERI RELASI DAN FUNGSI - Reni Novianti; Nurmaningsih; Rahman Haryadi (Program Studi Pendidikan Bahasa Inggris IKIP PGRI Pontianak, 2022)
This study aims to analyze students' problem-solving skills in relation and function material. The research method used is qualitative research in the form of descriptive research. The subjects in this study were class VIII students of SMP Negeri 2 Meliau. The data collection technique used in this research is measurement so that the data collection tool is in the form of a test. The data analysis technique used is descriptive statistics. The results of this study are (1) only 63.87% of students are able to answer the problem-solving ability on the indicator of understanding the problem, (2) only 44.47% of students are able to answer the problem-solving ability on the indicator of planning for completion, (3) only 38.90% of students were able to answer the problem-solving ability on the indicator of implementing the completion plan, (4) only 27.76% of the students were able to complete the problem-solving ability on the indicator of Checking Back. So in general it can be concluded that the problem solving ability of class VIII students of SMP Negeri 2 Meliau is low.